2022
DOI: 10.3390/jcm11071978
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Efficacy and Long-Term Outcomes of Patients Treated with the Occlutech Paravalvular Leak Device for Significant Paravalvular Regurgitation

Abstract: Between December 2014 and March 2021, 144 patients with aortic (Ao) or mitral (Mi) paravalvular leaks (PVLs) were enrolled at 21 sites in 10 countries. Safety data were available for 137 patients, who were included in the safety analysis fraction (SAF), 93 patients with Mi PVLs and 44 patients with Ao PVLs. The full analysis set (FAS) comprised 112 patients with available stratum (aortic/mitral leak) as well as baseline (BL), 180-day or later assessments (2 years). Procedural success (implantation of the devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…To date, there are only three studies reporting long-term outcomes ≥2 years after percutaneous mitral PVL closure procedures [ 24 , 27 , 28 ]. In 2017, Alkhouli et al reported a long-term survival rate of 50.3% following percutaneous mitral PVL closure in 195 patients, with a mean follow-up period of 3.7 ± 2.7 years [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, there are only three studies reporting long-term outcomes ≥2 years after percutaneous mitral PVL closure procedures [ 24 , 27 , 28 ]. In 2017, Alkhouli et al reported a long-term survival rate of 50.3% following percutaneous mitral PVL closure in 195 patients, with a mean follow-up period of 3.7 ± 2.7 years [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Alkhouli et al reported a long-term survival rate of 50.3% following percutaneous mitral PVL closure in 195 patients, with a mean follow-up period of 3.7 ± 2.7 years [ 24 ]. More recently, Onorato et al described a 91.3% technical success rate employing the dedicated Occlutech PVL device (Occlutech, GmbH, Jena, Germany) in a single-center registry including 93 mitral PVL and 44 aortic PVL procedures [ 27 ]. Overall mortality rate at 2 years was 8.3% in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as a co-author of Spanish Real World PVLs Closure Registry [ 3 ], and E.M.O. as the principal investigator and coordinator of the International Multicenter PLD Registries [ 4 , 5 ] with a cohort of more than 200 patients, and from their knowledge of the literature and other experts’ experience through regular case discussions.…”
Section: Methodsmentioning
confidence: 99%
“…The PLD has a special braiding that avoids a distal hub, giving flexibility and adaptability with a high success rate in achieving complete closure. In cases with large crescent-shaped defects requiring multiple vascular plugs, the implantation of a single large rectangular device to the edges increases the success rate and lowers residual regurgitation without interfering with the valve ( Figure 1 and Figure 2 , Supplementary Figures S1 and S2 ) [ 4 , 5 , 11 , 12 , 13 ].…”
Section: Pvl Regurgitation After Avr: Procedural Aspectsmentioning
confidence: 99%